Assessment of Microplastics in Hanumante River of Kathmandu Valley - Bhatta, Khageshwari; Sharma, Gauri Devi; Bohara, Khagendra Prasad; Joshi, Mahesh Kumar (Journal of Nepal Chemical Society, 2024)
Plastic debris is one of the most significant organic pollutants in the aquatic environment. Researchers are currently focusing on the impact of micro and nano-scale plastic waste on aquatic systems. In this study, we investigated the distribution of plastic pellets and fragments present in the freshwater ecosystem. The goal was to assess microplastic (MP) abundance in the Hanumante River, a tributary of the Bagmati River, and analyze their properties. Sample collection involved the bottle sampling method. Filtration, wet peroxide oxidation, density separation, gravimetric analysis, and microscopic examination were performed to study the characteristics of microplastics. The study was conducted by following the guidelines of the National Oceanic and Atmospheric Administration (NOAA) protocol. Gravimetric analysis was applied to calculate the reduced mass of the sample after total organic carbon reduction. Results showed that the maximum amount of reduced sample was obtained from the sample taken from sample taken from Madhyapur Thimi area (~3.593g) and the minimum amount of reduced sample was obtained from the sample taken from the Shiva temple Jagati area (~2.130g).  Microscopic inspection showed that samples taken from different locations were composed of an average of 14–23 microplastics per liter of sample. FT-IR analysis was performed to analyze the characteristics of microplastics and the type of polymers present in the sample which showed the abundance of polymer materials like polyethylene, polypropylene, and polycarbonates. The findings imply that appropriate plastic waste management measures be implemented in the communities to safeguard the ecosystem benefits derived from the river.